2017
DOI: 10.2147/hp.s117967
|View full text |Cite
|
Sign up to set email alerts
|

SNPs, linkage disequilibrium, and chronic mountain sickness in Tibetan Chinese

Abstract: Chronic mountain sickness (CMS) is estimated at 1.2% in Tibetans living at the Qinghai–Tibetan Plateau. Eighteen single-nucleotide polymorphisms (SNPs) from nine nuclear genes that have an association with CMS in Tibetans have been analyzed by using pairwise linkage disequilibrium (LD). The SNPs included are the angiotensin-converting enzyme (rs4340), the angiotensinogen (rs699), and the angiotensin II type 1 receptor (AGTR1) (rs5186) from the renin–angiotensin system. A low-density lipoprotein apolipoprotein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Studies of VEGFA SNPs in the pathogenesis of CMS have indicated that genetic variations of VEGFA have pathophysiological effects on CMS development [20, 26]. Here we found that the frequencies of the major alleles of rs699947, rs1570360, rs2010963, and rs3025039 in the Sherpa highlanders (0.824, 0.892, 0.667, and 0.833, respectively) were equivalent to those in heathy Tibetans dwelling on the Tibetan Plateau (0.828, 0.907, 0.567, and 0.897, respectively) (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of VEGFA SNPs in the pathogenesis of CMS have indicated that genetic variations of VEGFA have pathophysiological effects on CMS development [20, 26]. Here we found that the frequencies of the major alleles of rs699947, rs1570360, rs2010963, and rs3025039 in the Sherpa highlanders (0.824, 0.892, 0.667, and 0.833, respectively) were equivalent to those in heathy Tibetans dwelling on the Tibetan Plateau (0.828, 0.907, 0.567, and 0.897, respectively) (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variations of VEGFA are apparently related to pathophysiological effects affecting CMS susceptibility, likely through targeting transcription factor binding sites (TFBS) of VEGFA [20, 21, 26]. Hypoxia-induced gene expression was described as a transcriptional mechanism mediated by hypoxia-responsive elements (HREs) present in the promoter region in the 5′ flanking region of VEGFA [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Based on subgroup analysis, minor allele in East Asian was related to an increased risk of CRC. This SNP is located in 3'UTR of vascular endothelial growth factor gene which may affect hsa‐miR‐591 target sites . This gene affects angiogenesis, tumor growth, and metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…This SNP is located in 3'UTR of vascular endothelial growth factor gene which may affect hsa-miR-591 target sites. 186 This gene affects angiogenesis, tumor growth, and metastasis. 187 It is also related to CRC outcomes and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…VEGFA is a signaling protein involved in the regulation of angiogenesis, vasculogenesis and endothelial cell growth. It induces endothelial cell proliferation, promotes cell migration, inhibits apoptosis and induces permeabilization of blood vessels.VEGFA is also a key regulator of hypoxia.There are several VEGFA SNPs associated with high altitude sickness that create alterations in punitive TFBS for the gene [26][27][28][147][148][149].…”
Section: Vascular Endothelial Growth Factor (Vegf)-amentioning
confidence: 99%